(untitled) (Nexo Revista Científica, 2023)
The study aims at determining the conceptual basis for the formation of digital sovereignty under the influence of external factors. The article uses the methods of content analysis and graphic modeling. The study shows external challenges that have the greatest impact on the formation of digital sovereignty of the state. Only international cooperation and respect for the digital sovereignty of individual countries can help ensure security during the global digital transformation.